The Relationship Between Knowledge, Information Exposure, and Cadre Support with Mothers' Visits for Under-Five Weighing Coverage in the Working Area of Pegambiran Health Center, Padang City, 2024 - Suherlis, Septia; Sriyanti, Roza; Meinapuri, Malinda; Ariadi, Ariadi; Afdal, Afdal; Firdawati, Firdawati (Journal La Medihealtico, 2024)
Malnutrition is a major nutritional problem throughout the world. The highest number of nutritional problems occured in East Africa and Asia, including Indonesia. The Indonesian Ministry of Health conducted a survey and revealed that in Indonesia, 1 in 12 toddlers suffered from wasting, and 1 in 5 toddlers suffered from stunting (SSGI 2022). The scope of toddler weighing at Pagambiran health center with the indicators of (K/S) 99,84%, (N/D) 53,26% and (D/S) 13,4%, had not reached the strategic plan target which was 85%. The strategy used to reduce nutritional problems was to increase community participation through integrated health posts (posyandu). The purpose of this study was to determine the determinant factors related to mothers' visits to posyandu on the scope of weighing toddlers. The research method used was the combination method (mix method). The research was conducted from September 2023 to August 2024. The number of samples was 196 mothers who had children aged 12-59 months in the work area of Pegambiran Health Center using the sampling technique of cluster random sampling. The data were collected through questionnaires and interviews. This research data analysis was carried out using univariate and bivariate analysis. The result of statistical test, it was found out that the relationship knowledge (p-value 0.002), exposure information (p-value 0.007) and cadre support (p-value 0.000) to mothers' visits in the scope of toddler weighing.The conclusion of the research is that there is a significant relationship between knowledge, exposure information and cadre support to mothers' visits in the scope of toddler weighing at the work area of Pegambiran Health Center.